SECONDARY SCHOOL ENROLLMENT IMPACT ON THE ECONOMIC AS AN ESSENTIAL INPUT OF CIVILIZATION - Zainal Ridho, Sari Lestari (Jurnal Ekonomi dan Studi Pembangunan, 2018)
Economic growth, an essential input to civilization, since economic growth spreads civilizations in various dimensions, in the sense of civilization as the liberation of people from their brute physical needs, giving them the opportunity to develop their individuality, their minds, and the quality of their lives. The economy of a country is influenced by many factors, one of the important factors that influences it is education. Hence, the purpose of this study is to examine the impact of education on the economy as an essential input of civilization, by comparing the two major groups of countries in the world, Islam and the West. These two major groups of countries that are often opposed, including in terms of the economic system implemented in both groups of countries. Since it is argued that Islamic nations apply a specific system of financial in the economy, namely the Islamic financial system, hence this research investigated the effect of both group nations (Islamic or non-Islamic) comparatively to the economy. The research method used in this research is quantitative approach, by using statistical analysis, multiple linear regression, as the method of data analysis, in order to obtain results that can be drawn conclusions as a result in this study. Based on the results in this study, it can be concluded that education has a positive and significant impact to the economy, as an input of civilization, although there are no different economic conditions between the Islamic (OIC member) Countries and non-Islamic one.